Minimally invasive Chevron-Akin osteotomy: clinical and radiographic results - Nunes, Gustavo; Magalhães, João; Baumfeld, Tiago; Pinto, Roberto (Journal of the Foot & Ankle, 2020)
Objective: To present the clinical and radiographic results of surgical treatment of patients with moderate to severe hallux valgus (HV) by minimally invasive Chevron - Akin osteotomy (MICA). Methods: The case series comprises 25 patients (30 feet) with diagnoses of moderate to severe HV treated surgically with the MICA technique. All patients answered the American Orthopedic Foot and Ankle Score (AOFAS) and rated pain on visual analogue scale (VAS) at preoperative assessment and at the last follow-up consultation. Radiological assessment included measurement of the valgus angles of the hallux (HVA) and the 1st and 2nd ray intermetatarsal angle (IMA). Complications and satisfaction ratings were also documented. Results: Mean follow-up was 14.6 months. Mean AOFAS increased from 42.8 to 90 and VAS reduced from 8.6 to 1.7. Mean HVA reduced from 31.7o to 8.4o and IMA from 14o to 5o. All these improvements were statistically significant (p<0.001). The most common complication observed was discomfort caused by hardware, affecting five feet (16.6%). Two patients (6.6%) had transitory neurapraxia and one patient (3.3%) developed reflex sympathetic dystrophy. There were no cases of infection, relapse, pseudarthrosis, or malunion of osteotomies. Subjective satisfaction ratings classified 93.3% of results as good or excellent. Conclusion: Minimally invasive Chevron-Akin osteotomy is a safe and reproducible technique that achieves good clinical and radiographic results for treatment of moderate to severe hallux valgus. Level of Evidence IV; Therapeutic Studies; Case Series.